PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Fitria , Meliana (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This community service was carried out in Karehkel Village, Leuwiliang District, Bogor Regency in June-September 2023. This activity aims to carry out Sharia financial planning for families in Karehkel Village. This community service activity is carried out using the observation method. Training, interviews and application implementation. The community, especially families in Karehkel Village, are also enthusiastic about this activity because they gain understanding and insight into sharia financial planning, especially for families in this village.